Another Judas and the Cross: Pseudo-Hebrew and the Politics of Conversion in the Judas Cyriacus Legend - Enlow, Loraine Schneider (Harvard theological review, 2025)
Judas Cyriacus appeared in liturgy, hagiography, iconography, and vernacular literature from late antiquity until the early modern era, enjoying wide popularity across Christian traditions. While the Finding of the Holy Cross has been well-studied, the invented saint, Judas Cyriacus, and his martyrdom have not received comparable attention. His legend’s entanglement with liturgical and vernacular traditions around the veneration of the cross, especially in the West, influenced Western Christian attitudes towards Jews for over a thousand years, warranting further study. This article examines the Judas Cyriacus legend, revealing the complexities of Christian identities and truth claims in late antiquity, especially in inter-religious contexts with contemporary rabbinic texts. It also explores the significance of Judas Cyriacus’ pseudo-Hebrew prayers, which both adapted intercultural magical practices for Christian use and marked his Jewish identity as indelible even during his Christian martyrdom, highlighting tensions in the perceived efficacy of Christian baptism for Jews.